Application value of metagenomic next-generation sequencing based on protective bronchoalveolar lavage in nonresponding pneumonia - Yingchen Pang; Junjin Qiu; Hong Yang; Junbao Zhang; Jianming Mo; Wendi Huang; Chao Zeng; Ping Xu (Microbiology Spectrum, 2025)
ABSTRACT This study aims to explore the application value of metagenomic next-generation sequencing (mNGS) of protective bronchoalveolar lavage fluid in the differential diagnosis and pathogenetic identification of nonresponding pneumonia. This study analyzed patient symptoms, auxiliary examinations including pathogen detection, and treatment response to identify the reasons for the lack of response to initial treatment and the pathogenetic diagnosis of pulmonary infections. The diagnostic efficacy of pathogen culture and mNGS was statistically analyzed and compared based on the clinical diagnosis criteria. (1) The two most common reasons for the ineffectiveness of initial treatment in nonresponding pneumonia cases are that (i) the initial treatment did not cover the pathogenic bacteria in pulmonary infection cases and that (ii) non-infectious pulmonary diseases were responsible. The most common pathogens in pulmonary infection cases of nonresponding pneumonia are Mycobacterium tuberculosis (MTB), Pneumocystis jirovecii, Aspergillus, and Pseudomonas aeruginosa. (2) In pulmonary infectious cases, mNGS demonstrated a higher detection sensitivity for pathogenic bacteria than pathogen cultures. mNGS combined with protective bronchoalveolar lavage has good clinical application value in the accurate diagnosis of pathogens and identification of non-infectious diseases.IMPORTANCEThe combination of mNGS and the protective BAL technique demonstrates significant utility in accurately diagnosing pathogens and identifying non-infectious diseases. Misdiagnosis of non-infectious lung diseases as infectious lung diseases is a common factor contributing to the lack of response to initial treatment in nonresponding pneumonia patients. The most common pathogens in pulmonary infection cases of nonresponding pneumonia are MTB, Pneumocystis jirovecii, Aspergillus, and Pseudomonas aeruginosa.